A Literature Review on the Cultural Perspective Study in Elementary School Education in Indonesia - Fitriadi Fitriadi; Risma Magaretha Sinaga; Rosida Rakhmawati Muhammad (Journal of Innovation in Educational and Cultural Research, 2024)
In Indonesia, the intricate tapestry of cultural diversity offers both unique opportunities and challenges within the educational sector. The integration of cultural context into education has garnered increasing interest, highlighting the potential for traditional practices and cultural nuances to significantly enhance learning outcomes. This study delves into the cultural dimensions of Indonesian basic education by conducting a comprehensive literature review, examining scientific inputs on the incorporation of cultural perspectives into the educational landscape. Utilizing a qualitative research methodology, the study embarked on a meticulous process of literature source identification, selection, data collection, analysis, and manuscript refinement. The synthesis of findings from diverse studies reveals that embedding cultural contexts and traditional practices, particularly in mathematics and music education, markedly benefits students' comprehension, learning experience, and overall academic growth. The research underscores the transformative impact of ethnomathematics and traditional music literacy, suggesting their inclusion in teaching methodologies to enrich educational content with Indonesia's rich cultural heritage. Moreover, the study identifies challenges such as implementation hurdles and the need for pedagogical innovation, advocating for ongoing research to assess the broader impacts of culturally responsive education on students' multifaceted development across various cultural settings. This exploration establishes a foundation for further academic inquiry and practical application, emphasizing the necessity of a culturally enriched educational framework that respects and promotes Indonesia's diverse cultural identity while fostering academic excellence and social cohesion.